2013
DOI: 10.1063/1.4809792
|View full text |Cite
|
Sign up to set email alerts
|

Development of an (e,2e) electron momentum spectroscopy apparatus using an ultrashort pulsed electron gun

Abstract: An (e,2e) apparatus for electron momentum spectroscopy (EMS) has been developed, which employs an ultrashort-pulsed incident electron beam with a repetition rate of 5 kHz and a pulse duration in the order of a picosecond. Its instrumental design and technical details are reported, involving demonstration of a new method for finding time-zero. Furthermore, EMS data for the neutral Ne atom in the ground state measured by using the pulsed electron beam are presented to illustrate the potential abilities of the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…For this purpose, we performed numerical calculations of the laser-assisted cross sections for two laser-field geometries, LP and LP⊥, using different trial wave functions of He. In the case of the laser-field parameters that can be realized in the upcoming measurements, 18 we found that the laser-assisted momentum profiles are weakly sensitive to the model of the He ground state when the He + ion remains in the n = 1 state. In contrast, when the He + ion is left both in the n = 2 state and in the continuum state, the results strongly depend on the employed He wave function.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For this purpose, we performed numerical calculations of the laser-assisted cross sections for two laser-field geometries, LP and LP⊥, using different trial wave functions of He. In the case of the laser-field parameters that can be realized in the upcoming measurements, 18 we found that the laser-assisted momentum profiles are weakly sensitive to the model of the He ground state when the He + ion remains in the n = 1 state. In contrast, when the He + ion is left both in the n = 2 state and in the continuum state, the results strongly depend on the employed He wave function.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17] At the present stage, an apparatus for (e, 2e) EMS has been developed which, in combination with a sufficiently high intensity laser, lends an opportunity for conducting laser-assisted EMS measurements. 18 The first theoretical analysis of the laser-assisted EMS method 15 was carried out for the case of atomic hydrogen, which is a benchmark system for EMS. However, from the viewpoint of experimental realization, a helium atomic target is more convenient and "easy-to-use".…”
Section: Introductionmentioning
confidence: 99%
“…Following Refs. [21,22], the laser frequency and intensity are set to co = 1.55 eV and / = 5 x 10" W /cm 2, respectively. They give for the electric-field amplitude the value Fq % 4 x 10-3 a.u.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, an EMS apparatus is being developed for combination with a sufficiently high intensity laser [22]. This opens a door for conducting laser-assisted EMS measurements in the very near future.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, use of an ultrashort-pulsed incident electron beam, which is the primary requirement of conducting EMS experiments for short-lived transient species, imposes an additional difficulty; if the intensity of the ultrashort-pulsed incident electron beam is increased, space charge effects may disturb the measurements by significantly broadening not only the temporal width but also the energy spread of the electron packet [12]. Under these circumstances, we have very recently developed a time-resolved EMS (TR-EMS) apparatus [13] based on the latest technological achievement in the instrumental sensitivity for traditional EMS [14].…”
mentioning
confidence: 99%